Killer Cupid - Berenson, Laurien (Berenson, Laurien. Melanie Travis mystery, 2023)
Melanie Travis is taking a much-needed break from the dog show circuit for a romantic Valentine's trip with her husband Sam, but when someone at their cozy Berkshires inn has an unexpected date with death, Melanie must slip into something sleuthier for the weekend... Melanie is delighted at the prospect of three uninterrupted days alone with Sam (and, of course, her prize-winning Standard Poodle, Faith). They're booked at the White Birch Inn, a picturesque New England resort nestled at the foot of a snow-covered mountain. The inn has a full slate of couples activities planned for the busy Valentine's weekend--date nights, sleigh rides, tobogganing, ice skating, and pop-up shops in the inn's ballroom --from the bubbly to the bubble bath, the resort is a perfect match for Melanie and Sam's vacation. But the first night of festivities feature an event that isn't on the program: murder. The sheriff quickly launches an investigation, but at the inn keeper's urging--and because she suddenly finds herself a person of interest in the case--Melanie tries to sneak a little detective work into her romantic getaway. But with the resort nearly sold out for the holiday weekend, there's no shortage of suspects, and Melanie's secret sleuthing is already attracting the wrong kind of attention. Her Valentine's trip is heating up faster than the chocolate fondue...just not in the way Melanie hoped. But if she doesn't catch the cold-hearted killer soon, another innocent victim will get the kiss of death...